Alterations in redox homeostasis following repeated sprint training - Marijančević, Domagoj; Vrkić, Nada; Jukić, Igor; Bok, Daniel (2020)
This study examined the effects of a 6-week repeated sprint training on redox-based homeostasis and their association with muscle damage. Fifteen male physical education students (aged 20.0±1.0 years; body weight 77.7±6.0 kg; height 181.0±4.4 cm; %body fat 8.7±3.0 %), familiar with intermittent activities, volunteered to participate in the study. Experimental training program consisted of 2-3 sets of 6-10 straight-line or shuttle 20-m repeated sprints with departures every 25 seconds and a 2-minute inter-set passive recovery. The training intervention lasted six weeks during which 18 training sessions were performed. The levels were measured of the following: 15-F2t-isoprostanes in plasma and 24-hour urine; superoxide dismutase, glutathione peroxidase and glutathione reductase in erythrocytes; uric acid and creatine kinase in serum after the first and the penultimate training session. The level of muscle damage following the repeated sprint exercise was not significantly altered (402 to 496 U/L; p=.151) and had no significant associations with the changes in markers depicting redox-homeostasis. A significant increase in plasma 15-F2t-isoprostanes (0.32 to 0.56 ng/mL; p=.026), and a subsequent decrease in glutathione reductase (7.7 to 3.4 U/g Hb; p<.001) were observed. Urinary 15-F2t-isoprostane levels were 25% greater at post-training, although this increase did not reach statistical significance. These results indicate that repeated sprint training stimulates the equilibrium in redox homeostasis developing antioxidant protection to the constantly increasing training load.
Bibliografija: str. 27-29.
Summary.
Keywords: Trening -- Trening visokog intenziteta -- Oštećenje mišića -- Oksidativni stres